Central Nervous System Associated With Light Perception and Physiological Responses of Birds - Kang, Seong W. (Frontiers in Physiology, 2021)
Environmental light that animal receives (photoperiod and light intensity) has recently been shown that it affects avian central nervous system for the physiological responses to the environment by up or down- regulation of dopamine and serotonin activities, and this in turn affects reproductive function and stress-related behavior of birds. In this article, we speculate on the intriguing possibility that one of the proposed avian deep brain photoreceptors, melanopsin (Opn4), may play roles in the dual sensory-neurosecretory cells in the hypothalamus, midbrain, and brainstem for the behavior and physiological responses of birds by light. Specifically, we have shown that the direct light perception of premammillary nucleus dopamine-melatonin (PMM DA-Mel) neurons is associated with the reproductive activation in birds. Although further research is required to establish the functional role of Opn4 in the ventral tegmental area, dorsal raphe nucleus, and raphe nuclei in the light perception and physiological responses of birds, it is an exciting prospect, because the previous results in the PMM support this hypothesis that Opn4 in the midbrain DA and serotonin neurons may play significant roles on the light-induced physiological responses of birds. One of the potential deep-brain photoreceptors, Opn4, in the midbrain and brainstem of birds will be discussed.